Effects of external Chinese herbal therapy combined with pulse electromagnetic field on older adults with knee osteoarthritis: study protocol for a randomized controlled trial - Li, Xiang; Li, Foxiao; Yu, An; Bu, Qi; Wang, Ruirui; Li, Lijing; Zhang, Wei; Yang, Lei (Frontiers in Medicine, 2025)
IntroductionKnee osteoarthritis (KOA) is a major cause of disability, and both external Chinese herbal therapy (ECHT) and pulsed electromagnetic field (PEMF) therapy have shown potential in managing KOA symptoms. However, no research has directly compared the efficacy of ECHT, PEMF, and their combined use on pain relief and functional improvement in older adults with KOA. This highlights a significant research opportunity to explore the comparative benefits of these treatment modalities.Methods and analysisThis randomized controlled trial (RCT) aims to enroll 124 older adults with KOA and will randomly allocate them across four treatment groups: (1) exercise with health education, (2) exercise with ECHT, (3) exercise with PEMF therapy, and (4) exercise with a combination of ECHT and PEMF. Each intervention will be administered five times per week for 4 weeks. The primary endpoints are pain and functional capacity, while secondary measures encompass lower limb range of motion, alignment, joint space, and serum cytokine levels. Assessments will be conducted at baseline, post-intervention, and at the 4-week follow-up.DiscussionThis trial is poised to conduct a thorough comparative analysis of the impacts of ECHT, PEMF therapy, and their combined application in older adults with KOA. The study findings will not only inform clinical practice by offering data-driven recommendations but also enrich the scientific discourse on the complex interplay between inflammation, pain, and function in KOA.Clinical trial registrationChinese clinical trial registry platform: www.chictr.org.cn (no. ChiCTR2400087644).